Analisis Beban Kerja terhadap Kinerja Karyawan Melalui Stres Kerja Sebagai Variabel Intervening pada PT Bank Sumut Cabang Stabat - Syafa Davy Baihaqi Saragih; Yeni Absah; Anizar Anizar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the influence of workload variable on employee performance through work stress as an intervening variable at PT Bank Sumut of Stabat Branch. This study was used a quantitative method with the census method as a sampling technique and the structural equation model (SEM) method as a data analysis technique. The population in this study was 57 which the entire population was the sample. The data collection method used a questionnaire and data analysis was assisted by SmartPls 4. Based on the analysis, it was found that workload had a negative and insignificant effect on employee performance with T-Statistic value of 1.3467 and p-value of 0.178. The workload has a positive and significant effect on work stress with T-Statistic value of 2.771 and p-value of 0.006. The work stress has a positive and significant effect on employee performance with T-Statistic of 2.427 and p-value of 0.015. The workload has a positive and significant effect on employee performance through work stress with T-Statistic value of 2.585 and p-value of 0.010.